Fast SPICE-compatible simulation of low-power on-chip PWM DC–DC converters with improved ripple accuracy - Burcea, Florin (2019)
The circuit averaging technique has long been used as the basis for modeling the behavioral effects of switched-mode pulsewidth-modulated (PWM) dc-dc power converter circuits due to its simplicity and efficiency in simulation. However, circuit-averaged models struggle to capture the effects of higher order harmonics on the output waveforms. Alternatively, multiharmonic models that capture high-frequency characteristics of output waveforms are typically very complex and computationally expensive. A general, efficient, and accurate multiharmonic modeling and simulation technique for low-power on-chip PWM dc-dc converters is presented in this article. The technique is based on the large-signal averaged model of the PWM switch cell and on the Fourier series expansion of the typical converter waveforms. Its applicability range includes current-mode-controlled dc-dc converters. The method is exemplified on a buck and on a boost converter and achieves a speedup of one order of magnitude with an accuracy loss below 3% over the transistor-level simulation. The method accounts for nonideal circuitry and supports any number of harmonics.